Validation of the WIMU PRO™ device for jump detection in beach volleyball: a gender-based analysis during official competitions - Marzano-Felisatti, J. M; Pino-Ortega, J.; Garcia-de-Alcaraz, A.; Portillo, J.; Guzmán-Luján, J. F.; Priego-Quesada, J. I. (Journal of Human Kinetics, 2025)
Jump monitoring has become an essential procedure for training load management and injury prevention in many sports, such as beach volleyball. This study aimed to assess the validity of WIMU PROTM devices for jump detection in beach volleyball and to determine, in a preliminary way, whether gender, the player's individuality or the technical action associated with the jump could influence data accuracy. Eleven beach volleyball players (6 female and 5 male) were recorded with high-definition cameras and the WIMU PROTM device during 42 one-set official matches. The number of jumps recorded by the device was compared with the observational analysis. The instrument's sensitivity was calculated based on true positives and false positives/negatives in terms of gender, player individuality, and the type of the jump. The WIMU PROTM device presented great sensitivity (96.29%), with a lower gender difference (male = 97.20%, female = 94.56%) and higher inter-player variability in females (91.06%-98.08%) than males (95.02%-98.40%). Regarding the type of the jump, actions classified as "Others" (99.10 %) obtained the greatest sensitivity, followed by "Block" (97.25 %), "Spike" (95.75 %) and "Serve" (94.69 %). The WIMU PROTM is a valid device for automatic jump detection in beach volleyball. The variations observed in terms of gender, players' individuality, and the type of the jump highlight the importance of a context-specific individualized algorithm adjustment.